Repositórios de objetos de aprendizagem de língua portuguesa no ensino fundamental: alternativas para professores - Iudesneider, Rosenês Luzia [UNESP] (2015)
Today is commonplace seeing children and young people using technology to communicate, interact, information or even for fun. These people share information, exchange ideas, send photos and videos, make use of games, talk, among other activities. Young people today spend more time online and relating to each other over the internet, than in any other medium. Given this situation, the school needs to fit the new reality. This Portuguese research aims to investigate, through a qualitative research, the following educational alternatives in teaching Portuguese language through the use of internet. More specifically, it is proposed to discuss and unravel favorable possibilities for action amid a still arid set of tools that the teacher has. This dissertation also proposes to analyze what we have in terms of options on the internet and to anticipate the need for a detailed survey of sites and learning environments that do not simply transcribe pages of textbooks to the internet, but if proven as effective methods of aid to the teacher